LINEAR PERSPECTIVE AS A PRINCIPLE OF COMPOSITIONAL CONSTRUCTION OF A LANDSCAPE PAINTING (USING THE EXAMPLE OF IVAN TRUSH’S WORK) - Yamash, Yuri (European Science, 2025)
The monograph section presents a compositional analysis of Ivan Trush’s landscape paintings. Based on the research, the artist’s creative method is revealed to be based on the use of linear perspective in the landscape genre